CORRELATION OF THYROID-STIMULATING HORMONE AND PROLACTIN LEVELS IN NON-PREGNANT FEMALE - sinha, sulekha; HEGDE, ANUPAMA; A MANJREKAR, POORNIMA; MS, RUKMINI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to correlate prolactin (PRL) levels with different levels of thyroid-stimulating hormone (TSH). Methods: The study included 221 non-pregnant females of the age group of 16–43 years. TSH and PRL were assayed. Subjects were divided into three groups based on TSH levels, namely, low, normal, and high TSH levels and results compared. Statistical analysis: The comparison between different groups was done using test ANOVA. Correlation between TSH and PRL was established using Pearson’s correlation test. Results: Five subjects in Group-1 with low TSH values (mean 0.096±0.08 μIU/ml) had PRL 9.8±6.25 ng/dl, 186 subjects in Group-2 with normal TSH values (mean 1.98±0.94 μIU/ml) had PRL 16.58±8.78 ng/dl, and in Group-3 with high TSH values (mean 6.45±3.91 μIU/ml) had PRL 26.53±15.98 ng/dl. p value for TSH is <0.001 (significant) and for PRL also is <0.001 (significant). Positive correlation has been found in overall 221 subjects between TSH and PRL with correlation coefficient r=0.239 and p=0.01 (significant). Conclusion: PRL levels were higher in group with high TSH values. In most previous studies (subjects with established subclinical or overt hypothyroid), PRL was found higher with higher TSH levels. This study showed strong positive association between TSH and PRL irrespective of the thyroid status.